The how and why of electronic noses. - Nagle, H.T (IEEE spectrum)
Witnessing the swift advances in the electronic means of seeing and hearing, scientists and engineers scent a market for systems mimicking the human nose. Already commercial systems from several companies are targeting applications, present and potential, that range from quality assurance of food and drugs to medical diagnosis, environmental monitoring, safety and security and military use. Here, the authors outline the major transducer technologies-in one sense, the key component of an electronic nose